2001
DOI: 10.1038/35079100
|View full text |Cite
|
Sign up to set email alerts
|

ADP-ribose gating of the calcium-permeable LTRPC2 channel revealed by Nudix motif homology

Abstract: Free ADP-ribose (ADPR), a product of NAD hydrolysis and a breakdown product of the calcium-release second messenger cyclic ADPR (cADPR), has no defined role as an intracellular signalling molecule in vertebrate systems. Here we show that a 350-amino-acid protein (designated NUDT9) and a homologous domain (NUDT9 homology domain) near the carboxy terminus of the LTRPC2/TrpC7 putative cation channel both function as specific ADPR pyrophosphatases. Whole-cell and single-channel analysis of HEK-293 cells expressing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

35
990
8
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 819 publications
(1,043 citation statements)
references
References 13 publications
35
990
8
3
Order By: Relevance
“…cADPR, NAADP, and ADPR are involved in the regulation of cellular Ca 2+ homeostasis. While cADPR and NAADP trigger Ca 2+ -release from intracellular stores [5][6][7], ADPR controls calcium entry through the plasma membrane channel TRPM2 [8,9]. It is difficult to envision how cADPR and NAADP can function inside the cell if they are generated by ectoenzymes.…”
Section: Introductionmentioning
confidence: 99%
“…cADPR, NAADP, and ADPR are involved in the regulation of cellular Ca 2+ homeostasis. While cADPR and NAADP trigger Ca 2+ -release from intracellular stores [5][6][7], ADPR controls calcium entry through the plasma membrane channel TRPM2 [8,9]. It is difficult to envision how cADPR and NAADP can function inside the cell if they are generated by ectoenzymes.…”
Section: Introductionmentioning
confidence: 99%
“…In HEK293 cells, the expression of TRPM2 channel proteins was detected by Western blot analysis (Figure 4a). It is known that TRPM2 is only activated by intracellular ADPR that binds directly to TRPM2 channel's enzymatic NUDT9‐H domain in the C‐terminal tail 6. We tested whether extracellular administration of individual ADPR analogues had any effect on TRPM2 currents (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…It functions as an important Ca 2+ signalling regulator in a variety of cells, contributing to cellular functions including cytokine production, insulin release, cell motility, oxidative stress and cell death 5. TRPM2 is activated by reactive oxygen species (ROS) such as hydrogen peroxide and is considered as a chanzyme containing a unique C‐terminal Nudix hydrolase domain, that is homologous to the ADPR pyrophosphatase nudix hydrolase 9 (NUDT9) 6, 7, 8. The NUDT9‐homology (NUDT9‐H) domain serves a binding site for channel activation by adenosine 5′‐diphosphoribose (ADPR) 6.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human neutrophils have been shown to express a plethora of receptor-mediated, store-operated, and non-store operated calcium channels (Nunes and Demaurex, 2010;Demaurex et al, 1994;Heiner et al, 2003). TRPM2 channels, members of the transient receptor potential melastatin subfamily of ion channels, have been detected both on the plasma membrane (Perraud et al, 2001) and in lysosomes (Lange et al, 2009) of neutrophils and shown to enhance granule fusion and bactericidal activity (Hong et al, 2010). TRPM2 channels can be activated by ROS (Perraud et al, 2005) and play a key role in aggravating inflammatory processes by increasing the sensitivity to cell death (Yamamoto et al, 2008;Hara et al, 2002).…”
mentioning
confidence: 99%